Effects of blow molding ratio on mechanical properties of polylactide nanocomposite films - Żenkiewicz, M.; Richert, J.; Różański, A. (Polimery, 2010)
The results of the investigations of the effect of blow-up ratio of nanocomposite poly(lactic acid) (PLA) films on the mechanical properties determined under static tension are discussed. Investigated films contain additives in the form of a montmorillonite (MMT) nanofiller (LC sample) or MMT and poly(methyl methacrylate) (PMMA) as a modifier (LCM sample) or MMT and poly(ethylene glycol) (PEG) as a plasticizer (LCG sample). Using the X-ray diffraction (XRD) method, it was found that the screw shape of the co-rotating twin-screw extruder, applied to prepare a granulated nanocomposite, significantly influenced the dispersion of MMT within the PLA matrix. The PLA film containing the additives and subjected to a proper extrusion blow molding have better mechanical properties as compared to those of a neat PLA (L sample) film. These properties were found to be the best when the blow-up ratio (R) of the nanocomposite films was equal to 4. The images obtained by means of the transmission electron microscopy (TEM) confirmed that ordering of the MMT platelets within the PLA matrix occurred during the film blowing, which induced an improvement in the film mechanical properties. The presented results prove usefulness of the extrusion blow molding as a method of manufacturing nanocomposite films based on the PLA matrix.